Eternally vigilant : free speech in the modern era - Bollinger, Lee C., 1946-; Stone, Geoffrey R. (The University of Chicago Press, 2018)
While freedom of speech has been guaranteed us for centuries, the First Amendment as we know it today is largely a creation of the past eighty years. Eternally Vigilant brings together a group of distinguished legal scholars to reflect boldly on its past, its present shape, and what forms our understanding of it might take in the future. The result is a unique volume spanning the entire spectrum of First Amendment issues, from its philosophical underpinnings to specific issues like campaign regulation, obscenity, and the new media. "With group efforts, such as this collection of essays, it is almost inevitable that there will be a couple--and often several--duds among the bunch, or at least a dismaying repetition of ideas. Such is not the case here. . . . Whether one agrees with a given author or not (and it is possible to do both with any of the essays), each has something to add. Overall, Eternally Vigilant is a thoughtful and thought-provoking book, consistently intelligent and, at times, brilliant."--Richard J. Mollot, New York Law Journal Contributors: Lillian R. BeVier Vincent Blasi Lee C. Bollinger Stanley Fish Owen M. Fiss R. Kent Greenawalt Richard A. Posner Robert C. Post Frederick Schauer Geoffrey R. Stone David A. Strauss Cass R. Sunstein.